Sociodemographic determinants of good hygience practices among the indigenous primary caregivers of under three children in Malaysia - Zakaria, Liyanatul Najwa; Minhat, Halimatus Sakdiah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Poor hygiene practice is an important factor that lead to morbidity and mortality among young children which are common among the indigenous population due to the lack of access to health services and their unique beliefs and practices. This study aimed to identify the socio-demographic determinants of hygiene practices among the indigenous (known as Orang Asli in Malaysia) primary caregivers of children under the age of three in Malaysia. Methods: A cross-sectional study was conducted among 166 primary caregivers of Orang Asli children of below three years old in Kuala Langat District. Data was collected using a validated and pre-tested questionnaire via face-to-face interviews with individual respondents. The questionnaire consisted of two main sections: sociodemographics and hygiene practice. Results: A majority of the Orang Asli primary caregivers had good hygiene practices (78.9%). The number of children under five years old living at home was significantly associated with hygiene practice and it was the only significant determinant or predictor of good hygiene practice among the Orang Asli primary caregivers. Conclusion: The number of children under five years old living at home is an important factor to ensure good hygiene practices among the primary caregivers of Orang Asli children. This factor need to be taken into consideration in monitoring children health status by the health staff by emphasizing the importance of hygiene practice in the prevention of infectious diseases and malnutrition among Orang Asli children.